Innovation and development in agricultural and food systems - Faure, Guy; Chiffoleau, Yuna; Goulet, Frédéric; Temple, Ludovic; Touzard, Jean-Marc (éditions Quae, 2018)
Innovation is often presented as one of the main catalysts for more sustainable and inclusive development. In the agricultural and food sectors, innovation is characterized not only by specificities arising from its relationship to nature, but also from the wide diversity of its stakeholders, ranging from farmers to consumers, and including intermediaries such as the research community and advisory services. Innovation emerges from interactions between these actors, who mobilize resources and produce knowledge in collaborative mechanisms in order to generate changes. It encompasses domains as varied as production practices, market organization, and eating habits. Innovation is closely tied to major development challenges in its various forms: agroecological innovation, social innovation, territorial innovation, etc. This book casts a look at innovation in agricultural and food systems. It focuses in particular on supporting innovation, by examining methods and organizations, and on evaluating innovation using different yardsticks. The book is based on reflections and research originating from various scientific disciplines, on fieldwork carried out both in France and in many countries of the Global South, and finally on the experiences gained by accompanying and supporting innovative actors. It combines theoretical contributions on innovation with iconic case studies to illustrate its observations and discussions. This book is intended for teachers, professionals, students, and researchers.